(untitled) (Research, Society and Development, 2021)
The objective was to present reflections on the contributions of the Maria Montessori Method in a current context, considering the development of the child’s autonomy in the early years of Basic Education. As for the method, a bibliographic review research was carried out, taking into account the contributions of several authors, observing the characteristics of Montessori Padagogy and its methodological and didactic reflections on the development of children’s autonomy in basic education and its performance in Brazil, succeeding with the theoretical and methodological approach of Traditional Pedagogy and of Waldorf Pedagogy to support the reflective analysis of the Montessori model. With the results, it was noticed that Montessori Pedagogy is present in 62 educational units distributed in all Brazilian regions, which can be understood as a pedagogical alternative aligned with the regulatory principles of BNCC and PCN, and there was a lack of studies that point to the development of Montessori Pedagogy in public schools that provide services to Early Childhood Education and Elementary Education. It can be concluded that Montessori Pedagogy has been making a significant contribution to the learning of children in their educational development with autonomy and freedom, and through playful approaches and application of the model in cycles by age group, stimulates the construction of knowledge and better interaction in the educational environment.